(untitled) (Research, Society and Development, 2020)
The objective is to verify the cure rate and treatment abandonment rate of people with tuberculosis notified in the State of Rio Grande do Sul from 2006 to 2016. Methodology; retrospective cross-sectional study through the Health Information:System using the Information and Diseases of Notifications, including notifications for tuberculosis in the period from 2006 to December 2016 and residents in Rio Grande do Sul. Results: the closure of cases classified as abandonment was 16%, the average cure rate was 76%, deaths from other causes a average rate of 18% and the rate of deaths from tuberculosis in the analyzed period was 4%. Conclusion; it that the majority of gauchos notified by tuberculosis are undergoing treatment and have consequently been cured, however, the dropout rate is high. It is necessary to rethink strategies as recommended by the Ministry of Health to control this disease.